PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA ELEVEN CAFE BENGKULU - Sri Ekowati; Meilaty Finthariasari; Aslim Aslim (Universitas Muhammadiyah Bengkulu, 2020)
This research is based on the importance of prices and promotion of purchasing decisions. The formulation of the problem is whether prices and promotions have a positive effect on purchasing decisions. This study aims to examine and analyze the influence of prices and promotion of product purchasing decisions at Eleven Cafe Bengkulu. The object of this research is Eleven Cafe Bengkulu consumers with an accidental sampling method, which the respondent explained in this study was 65 people. Data collection method using questionnaire.The results of this study can be concluded that seen from the test of multiple linear regression equation using the SPSS program, namely Y = 20.416 + - 312X1 + 185X2. The results of the analysis found that prices negatively affect purchasing decisions and promotion has a positive effect on purchasing decisions. The testing of the t test hypothesis shows that both variables have an influence on the purchase decision of Adjusted R squer's number of 0.122 indicating that 12.2 percent of purchase decisions can be explained by the two independent variables used in the regression equation, while the rest is influenced by other variables not included in this study.Â Keywords: Price, Promotion, Purchase Decision.